Faktor-Faktor Yang Berhubungan Dengan Kinerja Karyawan Di RS Kartika Kasih Sukabumi - Hans Widjaja Putra; Cicilia Windiyaningsih; Nurcahyo Andarusito (LPPM Universitas Respati Indonesia, 2020)
Kartika Kasih Hospital experienced an increase in the number of patients in 2019 by 28.1% compared to 2018 and the number of BOR 78.6% this increase had an impact on decreased employee performance. The results of performance measurement in 2019 found that 59.5% of employees underperform. The research objective is to analyze and prove the effect of individual characteristics, motivation, work environment, and job satisfaction on employee performance. The applied research method, cross-sectional design with a sample of 122 employees out of 173 employees who fall into the inclusion criteria. The object of research at Kartika Kasih Hospital which is located at Jl.Jend. A Yani No 18 A, Sukabumi City in December 2019-July 2020. Collecting data with mental capacity tests and questionnaires that have been tested for validity and reliability. The results of the study using binary logistic regression analysis prove that education, length of work, mental capacity, work motivation, satisfaction, and work environment together have an effect of 33.7%. The mental capacity variable is the dominant variable having an OR value of 3,460 (95% CI, 1,145-10,457), the work environment variable has an OR value of 2,636 (95% CI, 1,080-6,434), the education variable has an OR value of 1,380 (95% CI, 0.508- 3,749), the length of work variable has an OR value of 0.398 (95% CI, 0.136-1.165), the motivation variable has an OR value of 0.187 (95% CI, 0.077-0.453) and the satisfaction variable has an OR value of 0.457 (95% CI, 0.193-1.083) ). There is no relationship between age, gender, and basic personality on performance. Suggestions for conducting regular evaluations to determine the mental capacity of employees to make positive changes, analyzing workloads with salary compensation, conducting good supervision, and evaluating motivation, satisfaction, and work environment